CONSULAR ASSISTANCE FOR NATIONALS DETAINED BY A FOREIGN GOVERNMENT: STATES’ POLICIES AND PRACTISES - Dewi Avilia (Indonesia Law Review, 2017)
The Vienna Convention on Consular Relations of 1963 outlined the rights of a state to exercise its obligation to protect the interests of its nationals abroad. The protection given by states to their nationals is commonly referred to as consular assistance. The main objective of consular assistance is to help nationals facing difficulties abroad. In the event of an arrest, the aim of the provision of consular assistance is to protect the inalienable rights of a foreign detainee. The inalienable rights inherent to all detainees are the right retain counsel, and to receive due process of law. Although the 1963 Convention on Consular Relations is the codification of international customary law with regard to states’ practises in protecting their nationals, the practises may vary from one state to another. This paper analyses the policy and practises adopted by a state to protect its nationals detained abroad and suggests effective policies to provide consular assistance based on the reviewed state practises and policies.